The Profits of Non-Native Teachers that Native Teachers are Not Good at - Surdyanto, Annas (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
The article discusses the profits of non-native English teachers based on literatures. Although native and non-native teachers are teachers who teach language with purpose to enable students communicate in a target language, they are not the same in some learning aspects. Non-native language teachers have more than one language that native teachers precisely have no much understanding on it. One of some advantages coming from non-native teachers is good methods in teaching and explaining grammar. Another profit of non-native teachers is a gift as motivating teachers that are able to give motivation to students. In addition, benefit of non-native teachers who are also the second language learners is the ability for translating word and sentence. Besides, having an ability to understand second language learner problems is also the advantage of non-native teachers. The article assumes that native English teachers are not always more superior than the non-native ones. There are advantages that make them considerable in language teaching. The advantages are the ability to understand second language learner problems, motivation, teaching method selections, translation skill. This study is expected to neglect that mainstream perspective on non-native speakers claiming that non-native teachers are not a considerable selection. Finally, this article is not intended to downgrade native teachers since they have, however, better language exposures and modelling.